Stromal Fat Content of the Parathyroid Gland A Study on 60 Autopsy Cases (Medicine Today, 2015)
Controversies prevail in literatures about fat content of the parathyroid glands and no histological study was done before to observe the change with increasing age in a Bangladeshi population. The aim of the study was to determine the percentage of stromal fat in the parathyroid glands in different age in a Bangladeshi population. This cross-sectional, descriptive study was done in the Department of Anatomy, Dhaka Medical College, Dhaka, from January to October 2011. A total of 207 post mortem parathyroid glands of were collected from 60 Bangladeshi people of different age (unclaimed autopsied dead bodies, within 24-36 hours of death without any sign of putrefaction). The samples were divided into three groups i.e. A (11-30years), B (31-60years), and C (61-90years). Tissue blocks of the parathyroid gland were fixed in 10% formol saline, cut at 5µm thickness and stained with routine Harris Haematoxylin and Eosin (H & E) stain. From each age group 20 best prepared slides were taken. The proportion of fat of the parathyroid gland was determined with the point counting Zeiss-I integrating eyepiece under the light microscope. The data were collected from the histological study and statistical analyses were done by one-way ANOVA test. All the statistical analyses were done by using SPSS 13.0 version. The mean amount of stromal fat was found 35.65±1.63%, 42.56±1.27%, and 46.38±1.54% in group A, B and C respectively. The differences among the groups were statistically significant (P 0.001). The percentage of stromal fat of the parathyroid gland was found to increase with age in Bangladeshi people.Medicine Today 2015 Vol.27(1): 1-3